Isolation, Purification, Identification and Oxidation Analysis of Walnut Globulin - Qian XU; Zhou CHEN; Qinghua WANG; Panpan HAN; Siting LI; Aijin MA; Yingmin JIA; Yuanrong ZHAN (Shipin gongye ke-ji, 2022)
In order to reveal the main composition of walnut globulin and its antioxidant activity in vitro, defatted walnut meal was used as raw material to separate and purify the globulin. And 2,2'-azido-bis(3-ethylbenzothiazoline-6-sulfonic acid) (2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid), ABTS) cationic radical scavenging ability was used to evaluate its antioxidant capacity, after further defatting, the crude walnut globulin extract was extracted according to the Osborne fractionation method, and then the main protein components were separated and purified by HiTrapTM CaptoTM Q anion exchange column and SephacrylTM S 100HR gel filtration column. The results showed that the prepared globulin protein content was 51.53%, accounting for 15.3% of the walnut protein, and the isoelectric point was 3.8. The results of sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed that the molecular weight of the purified main protein component was 10.1 kDa. The major protein component in the active state consists of a 7S globulin vicilin Car i 2.0101 and 2S albumin. It was found that both crude globulin extract and purified protein component had good scavenging ability against ABTS+·, with IC50 values of 0.302 and 0.075 mg/mL, respectively, indicating that the scavenging ability of purified protein component was increased by more than 4 times. The research results could provide a theoretical basis for the development and utilization of walnut globulin.